Temporal and Spatial Stability on the Population Structure of Consumed and Illegally Traded Big-Headed Amazon River Turtle in the Negro River Basin, Central Amazon, Brazil - Pezzuti, Juarez C. B.; Oliveira, Tamires; Pantoja-Lima, Jackson; Rebêlo, George Henrique; Félix-Silva, Daniely (Frontiers in Ecology and Evolution, 2022)
Freshwater turtles are a valuable food resource for riverine human communities and have been historically overharvested throughout all major tropical large river basins, with consequent gradual population decreases. Even species considered to be abundant are declining, and in many cases were brought to a condition of near extinction. The collection of adult females during breeding season on nesting beaches is considered a major factor in population decline and subsequent loss of food sources for humans. There is growing consensus that adult females constitute the category which turtle populations can least afford to lose. In the Negro River Basin, the podocnemidid big-headed Amazon River turtle, Peltocephalus dumerilianus, is heavily exploited for consumption and poached for illegal trade among riverine communities and cities. Between 1997 and 2002 and in 2019, we measured live turtles and carapaces of big-headed turtles in the city of Barcelos and its surroundings, and among the riverine families living in the Jaú National Park. We compared body sizes and sex ratios between areas, periods, and between consumed and traded individuals. We found no differences between areas, even those close to Barcelos and the ones belonging to remote areas where pressure levels are lower. The individuals consumed in Jaú National Park are larger than those poached for illegal trade in both areas. There was an increase in average size between 1997 and 2002. Sex ratio was slightly skewed toward males, which were larger, and did not differ between areas and periods. Results indicate stability on size of harvested populations, which may be supporting current extraction levels. Data suggest this could be related to the absence of adult female capture during nesting for this species. We recommend protection strategies for other Amazon Podocnemidid species that focus on the protection of nesting beaches and surrounding areas where adults occupy, specifically in areas under communal protection.